Parameters Affecting Residue Nitrogen Mineralization in Flooded Soils - Becker, M.; Ladha, J.K.; Simpson, I.C.; Ottow, J. C. G. (Wiley, 1994)
If N mineralization from organic residues could be matched to plant uptake, N loss will be reduced. However, it is important to understand the transformations of residues and their controlling factors. Six‐week phytotron and two‐season field experiments were conducted to determine the influence of soil properties, residue composition, and soil fauna on N mineralization in flooded soils. Seven legume species, three legume‐rice (Oryza sativa L.) straw combinations, rice straw alone, and an Azolla sp. were incorporated into two soils (an Andaqueptic Haplaquoll and a Tropofluvent) at 100 mg N kg−1 dry soil and incubated for 6 wk. Residue N release in clay was about twice that of sandy soil, but was not correlated with the residues' N, C/N, water, or polyphenol contents. Net N mineralization was correlated to lignin/N (L/N). In the field, Sesbania rostrata Brem. and Oberm. and S. emerus Taub were incorporated at 60 kg N ha−1 1 d before rice transplanting. Additionally, rice straw was applied at 30 kg N ha−1 alone or with S. rostrata. Soil exchangeable NH+4‐N in unplanted light and dark subplots was measured biweekly. As in the phytotron study, initial soil NH+4‐N accumulation rates were higher from residues with relatively low L/N (S. rostrata) than from materials with higher L/N (S. emerus and S. rostrata‐rice straw mixture). Soil invertebrates were absent from dark subplots, where residue N mineralization during the first 6 wk was 30% lower than in plots exposed to light. The L/N of an applied residue may be a suitable indicator for predicting its N mineralization rate in flooded soils. Soil invertebrates may play a role in N mineralization.